A Marosi Református Egyházmegye 1927. évi kettéosztása (A Bekecsaljai Református Egyházmegye létrejötte) - BEREKMÉRI, Árpád Róbert (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
The Division of the Reformed Diocese of Maros in 1927 (The Formation of the Reformed Diocese of Bekecsalja). The territory of the Reformed Diocese of Maros was modified in 1927, this being the second significant change in its history. In 1641, several parishes have left the diocese to form the Reformed Diocese of Görgény. The managing of a diocese, which by the first half of the 20th century represented 125 parishes, became a difficult task for the governing body. The idea of a territorial division came up in 1918, but only in 1922 was a decision made by the board of the Diocese. The lengthy splitting procedure, approved by the Board of Directors, ended on April 20, 1927, with the formation of the Reformed Diocese of Bekecsalja. Lajos Kolozsvári became the Dean of the new Church organization and Dr. László Dósa lawyer became the churchwarden. The Board of Directors rejected the appeal made against the election, and confirmed the new governing body of the Diocese on May 24, 1927. While the new diocese was not recognized by the Ministry of Culture and while neither the state nor the Board of Directors gave any aid for the settling in arrangements, the functioning of the diocese had to be managed through its own available budget.